COMPARATIVE ANALYSIS OF EXPERIENTIAL MARKETING BETWEEN MALE AND FEMALE CUSTOMER ONLINE SHOP(CASE STUDY AT FACULTY OF ECONOMIC AND BUSINESS SAM RATULANGI UNIVERSITY) - Manalu, Marchell F.; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2019)
Abstract: The emergence of e-Commerce in Indonesia resulted due to the growth of the Internet, affected people’s preference for online shopping. Customers will get a different experience and gain a different advantage while shopping online, especially for a fashion product. there are still a lot of complaints about customer experience that can affect the customer intention to buying goods from online experience, whether for man and women. In this globalization era, information is one of the most important thing, it can be seen as the massive development and growth in information technology and sure it cannot be separated from our daily life, since it is already become the part of human lifestyle right now. The beginning of this era is started with invention of what we called now Internet. Internet is really useful in terms of information sharing and to communicate or connect people that is not limited in region and time, and it also can be very useful for our daily life needs, for government bureaucracy, education needs, and trade. if we talk about trade and internet, it is really relatable right now, since e-Commerce thing is what we see as a trend in this era.Keywords: experiential marketing, e-commerce, male and female customer